Profile of Pediatric Deaths in Bellary District - Gururaj Biradar1 , Pavanchand Shetty H2 , B Suresh Kumar Shetty3 , Haneil Larson Dsouza2, V Yogiraj4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Study was conducted in VIMS bellary on cases brought for autopsy. The data was collected from the postmortem report of the body brought for autopsy.The study done on 607 pediatric deaths in retrospective manner. In this study it was found out that male mortality was higher in comparison to females. The vulnerable or susceptible age group among the studied sample was 12 to 18 years. Road traffic accident was found to be one of the major killers